The Development of a Nursing Practice Guideline for Preparation of Autologous Stem Cell Transplantation, Sunpasitthiprasong Hospital - Thima, Varachaya; Noimuenwai, Premruetai; Masuthon, Suthida (Journal of The Royal Thai Army Nurses, 2023)
The purposes of this research and development study were to 1) develop of a nursing practice guideline in preparing patients receiving autologous stem cell transplantation and 2) to study the results of a nursing practice guideline. The sample consisted of 20 patients who were planned to undergo autologous stem cell transplantation, and 10 professional nurses by purposive sampling method. The research tools consisted of 1) group discussion issues and 2) a nursing practice guideline developed by the researcher. Data collection included a questionnaire on patient anxiety, readiness for action, health behavior and satisfaction, and a professional nurse satisfaction. Five experts verified content validity of all the research tools and used to experiment and find the reliability. Data were analyzed by descriptive statistics and Wilcoxon signed rank test. The research findings were as follows. 1) The nursing practice guideline consisted of preparation of the patient and care team members at pre-transplantation, during- transplantation and post-transplantation. 2) the patient anxiety after using the developed nursing practice guideline was significantly less than before using the nursing guideline (p<.05), the readiness to practice health behaviors, patient satisfaction and the satisfaction of professional nurses after using the developed nursing guideline were significantly higher than before using the nursing guideline (p<.05)